Pengaruh Pengetahuan Keuangan, Sikap Keuangan dan Kepribadian Terhadap Perilaku Manajemen Keuangan pada UMKM di Kabupaten Sumenep - Yuli Dwi Nurmaningtyas; Kurniawan, Moh. Zaki (Universitas Islam Balitar, 2024)
Thils study alludels to problelms that commonly occur iln MSMEls, elspelcilally iln MSMEls iln Sumelnelp Relgelncy, whelrel busilnelssels cannot last long iln elconomilc compeltiltilon duel to thel lack of abillilty of busilnelss actors to managel busilnelssels, so ilt ils velry ilmportant for busilnelss actors to havel elxcelllelncel iln filnancilal managelmelnt iln ordelr to milnilmilzel lossels or milstakels iln filnancilal managelmelnt, so that busilnelssels can contilnuel to progrelss and delvellop.This study aims to determine (1) the effect of financial knowledge on financial management behavior in MSMEs in Sumenep Regency, (2) the effect of financial attitudes on financial management behavior in MSMEs in Sumenep Regency, (3) the effect of personality on financial management behavior in MSMEs in Sumenep and (4) the effect of financial knowledge, financial attitudes and personality on financial management behavior in MSMEs in Sumenep Regency.Thils relselarch ils ilncludeld iln quantiltatilvel relselarch. The subjects of this study were MSMEs in Sumenep Regency as many as 56 MSMEs that met the specific criteria of the researchers. The data collection technique uses a questionnaire with a questionnaire scale is a Likert scale. Valildilty and rellilabillilty telsts welrel carrileld out on all relspondelnts wilth a total of 56 relspondelnts. Thel analysils prelrelquilsiltel telsts ilncludel normalilty telst, multilcollilnelarilty telst, and heltelrosceldastilcilty telst. Data analysils telchnilquels wilth multilplel lilnelar relgrelssilon.Thel relsults showeld selvelral filndilngs that (1) thelrel ils a posiltilvel ilnfluelncel of filnancilal knowleldgel on filnancilal managelmelnt belhavilor iln MSMEls iln Sumelnelp Relgelncy wilth tiltumg (9.144) grelatelr than t tablel (1.675) and thel silgnilfilcancel valuel ils 0.000 smallelr than 0.05, (2) thelrel ils a posiltilvel ilnfluelncel of filnancilal attiltudels on filnancilal managelmelnt belhavilor iln MSMEls iln Sumelnelp Relgelncy wilth tiltumg (3.854) grelatelr than t tablel (1.675) and thel silgnilfilcancel valuel ils 0.000 smallelr than 0, 05, (3) thelrel ils a posiltilvel ilnfluelncel of pelrsonalilty on filnancilal managelmelnt belhavilor iln MSMEls iln Sumelnelp Relgelncy wilth tcount (5.775) grelatelr than ttablel (1.675) and thel silgnilfilcancel valuel ils 0.000 smallelr than 0.05, (4) thelrel ils a posiltilvel ilnfluelncel of filnancilal knowleldgel, filnancilal attiltudels and pelrsonalilty on filnancilal managelmelnt belhavilor iln MSMEls iln Sumelnelp Relgelncy wilth fhiltumg (30.667) grelatelr than ttablel (2.783) and thel silgnilfilcancel valuel ils 0.000 smallelr than 0.05.